(untitled) (International Journal of Applied Research in Management and Economics, 2022)
Today’s world is extremely fast moving, and customer requirements as well as the customer expectations are changing unpredictably day by day. Firms need to continuously innovate their business model in order to keep up with the dynamic environment. All these changes affect the role of the customer in the supply chain and the relationships between partners, customers, and companies. Furthermore, it disrupts firms’ strategies as well as their organizational structures, which forces companies to transform digitally as soon as possible. To respond to these changes and to remain competitive, firms need to adapt their existing business models and create value in new ways. To meet the new requirements, firms need to stay closer to their customers and identify new opportunities by creating value together with the customer (customer co-creation). This process can be supported by the digitalization and the usage of digital technologies, such as Big Data, Internet of Things and Artificial Intelligence. The goal of this paper is to give an overview of the combined research areas business model innovation and customer co-creation. A literature review has been performed to explore the emerging and undiscovered new field. Especially in the customer-centric, digital world, the value creation together with the customer plays a major role. Based on the literature future research avenues are identified and introduced.